AUTHENTICATION OF PATCHOULI OIL FROM VARIOUS GROWING REGIONS USING GC-MS METHOD WITH CHEMOMETRIC COMBINATION ON THE PRODUCTS IN THE MARKET - Nurani, Laela Hayu; Guntarti, Any; Milanie, Rida Dwi; Gandjar, Ibnu Gholib; Rais, Ichwan Ridwan; Prasasti, Dian; Edityaningrum, Citra Ariani (Universitas Muhammadiyah Magelang, 2024)
Adulteration in patchouli oil trade is an ancient practice, where additional substances like turpentine oil are added to increase volume and odor. Therefore, this research aimed to determine the composition of patchouli oil, considering variations in growing regions and potential adulteration in the products available in the market. The analysis was carried out using the Gas Chromatography-Mass Spectrormetry (GC-MS) method with a Principal Component Analysis (PCA) chemometric combination for authentication. The sample obtained from Bantul, Kulon Progo, and Purworejo was isolated through steam and water distillation. Subsequently, it was tested in accordance with SNI standard 06-2385-2006 and analyzed using GC-MS. The results were compared to the products on the market and processed using multivariate chemometric, namely PCA with Minitab 19 software. GC-MS analysis showed the presence of various compounds contained in the oil, including alcohol, alpha-guaiene, beta-humulene, seychellene, trans-caryophyllene, neoalloocimene, and beta-patchoulene. The combination of GC-MS and PCA chemometrics was able to distinguish patchouli oil from others and the products available on the market. PCA chemometric analysis showed that the patchouli oil from various growing regions had the same chemical components as essential oil. Furthermore, PCA chemometric analysis of market products also showed similar results but varied significantly from turpentine oil. This showed that the patchouli oil product available on the market did not contain turpentine oil.